High-resolution geological, petrological and geochemical investigation of the mid mid-lower c. 3.3 Ga Kromberg type type-section, Barberton greenstone belt, South Africa Africa - Ndlela, Sibusisiwe (Rhodes University, Faculty of Science, Department of Geology, 2021)
The geology of the SE limb of the Kromberg type-section, its origin and its evolution has remained controversial for more than five decades since its discovery by Viljoen and Viljoen (1969). Different lithostratigraphy and geodynamic models have been proposed that were centred around two end-member models, a continuous layer-cake stratigraphy model (Viljoen and Viljoen, 1969c, Lowe et al., 1999) or a tectono-stratigraphic model (de Wit et al., 2011, Furnes et al., 2012). Additionally, the Kromberg type-section mafic-ultramafic sequence represents a relatively thin, dismembered sequence compared to other formations or 'complexes' in the Onverwacht Group. Previous geology workers relied on the field interpretations for the construction of the geological architecture of the Kromberg type-section; but no petrographic analyses were conducted for accurate, integrated geological characterization of different rock compositions. To address controversies centred around the Kromberg type-section geology and geodynamic setting, this study is aimed at testing previously proposed stratigraphic and geodynamic models by integrating high-resolution geological mapping, petrography, mineral chemistry and whole-rock geochemistry to verify rock characterization. The aim is to accurately reconstruct the volcano-sedimentary architecture of the Kromberg type-section and to compare this to the results of previous fieldwork. Moreover, the manner in which the Kromberg sequence may relate to current Archean geodynamic models is evaluated, and a new model explaining the origin and evolution of the Kromberg type sequence is proposed. The integration of high-resolution field mapping, petrography and geochemistry has allowed for a high precision study and that has resulted in the construction of a new geological architecture for the SE limb of the Kromberg type-section. The stratigraphic thickness of the SE limb of the Kromberg sequence comprises dominant c. 80% volcanic rocks and minor c. 15% intrusive rocks, intercalated by 7 volcano-sedimentary chert horizons (c. 5%). Four main rock types (groups) are present in the Kromberg type-section with two sub-types of komatiitic basalts (the Badplaas-type and Geluk-types), Fe-rich tholeiitic basalt, cumulate peridotite, and a metadunite. Although the Kromberg type-section records sub-greenschist to lower greenschist facies, more than 50% of the rock samples classify as altered with parts of the stratigraphy recording extensive chloritization and severe ocean-floor silicification. Geochemical data revealed an enrichment in SiO2, K2O, Ba, Rb and variation in HREE for highly silicified samples whereas, chloritized samples are enriched in FeO and have concave upward LREE patterns. Partially chloritized tholeiites and komatiitic basalts have overlapping SiO2 signatures, relatively flat REE patterns and a small negative Nb anomaly in the primitive mantle-normalized spider diagrams. This thesis provides the first Lu-Hf isotope data on whole rock samples from the Kromberg type-section. The ÎµHf values at t=3.33 Ga range between -0.62 to +4.18 and Hf model ages range between 3.43 - 4.27 Ga. The rock compositions are compared to the geochemistry of other greenstone belt rocks, which are considered to provide insight onto the geodynamic setting under which the Kromberg mafic-ultramafic sequence formed. The rock compositions reveal plume-related processes where a primitive mantle melt interacts with recycled mafic crust or mafic lower crust of older units of the Onverwacht Group. Only a small Nb anomaly is found in some samples and the data plots outside the subduction zone (forearc and back-arc) field. Rare-Earth element profiles are flat and not consistent with a subduction zone signature, as proposed in previous studies. Rifting of an oceanic floor in a juvenile basin is proposed for the formation of the Kromberg type-section rocks, prior to being tectonically accreted during regional transpressional deformation at c. 3.23 Ga.
Keywords: Petrology -- Eswatini and -- South Africa -- Barberton Greenstone Belt; Geology -- Eswatini and -- South Africa -- Barberton Greenstone Belt; Geochemistry -- Eswatini and -- South Africa -- Barberton Greenstone Belt; Onverwacht Group (South Africa); Barberton Greenstone Belt (Eswatini and -- South Africa); Groups (Stratigraph) -- South Africa